Hydrocotyle verticillata Thunb. (Apiaceae) - A new angiospermic record for Bangladesh (Bangladesh Journal of Plant Taxonomy, 2010)
Not available.Keywords: Hydrocotyle verticillata; new record; Bangladesh.DOI: 10.3329/bjpt.v17i1.5398Bangladesh J. Plant Taxon. 17(1): 105-108, 2010 (June)